Using silicate solubilizing bacteria as biocontrol agent to suppress Rigidoporus microporus causing white root rot disease of rubber - Ayob, Nurul Shakirah (2021)
White root rot disease (WRD) caused by Rigidoporus microporus is the most prevalent disease in rubber plantation. Current treatment using chemicals has caused environmental pollution and health hazard. An alternative curative for WRD using microbes to degrade naturally occurring silica (Si) in soil has potential to reduce disease incidence of WRD. Si is a beneficial element for plant growth and its amount in soil is abundant. However, Si availability is relatively low due to strong bonding with other elements in soil. The most important aspect in this research is to make full use of the role of microbes to mineralize silicon in soil for plant uptake against stresses despite promoting plant growth. Thus, the goals of this research were: (i) to isolate and screen potential microbes for its ability in mineralizing silicon, suppressing fungal growth and secreting plant growth promoting (PGP) traits, (ii) to study mechanisms of silicon solubilization by bacteria and (iii) to evaluate efficacy of silicate solubilizing bacteria (SSB) applied at different rates on determination of silicon uptake, inhibition of R. microporus, stimulation of induced systemic resistance (ISR) and enhancement of plant growth. To reveal the ability of the potential microbes on reducing disease occurrence of WRD, soil samples under rubber rhizosphere of various ages were collected to select bacteria with silicate solubilizing property, antagonism and plant growth promotion traits. Mechanisms underlying silicate solubilization by selected isolates were conducted. Finally, rubber seedling infected with R. microporus was challenged with SSB applied at different rates for 16 weeks to evaluate its effectiveness on reducing disease incidence, solubilizing natural silica in soil and promoting plant growth. Results showed that 3 isolates identified by 16S rRNA as Bacillus sp. strain NSAMYKJ16 (SSB16), Proteus sp. strain NSAMYKJ18 (SSB18) and Bacillus sp. strain NSAMYKJ21 (SSB21) were able to mineralize insoluble silicate, inhibit growth of R. microporus and produce PGP traits. It was found that all SSB were able to dissociate silicate minerals up to 14 days with reduction in pH of the cultured medium. Tartaric and succinic acids were major acids involved in solubilization process of silicate minerals by all SSB. In the study of the effect of pH, it was found that all SSB released maximum silicic acid at pH 9 tested on quartz. Meanwhile, magnesium trisilicate was best dissociates only by SSB18 observed at pH 3, pH 6 and pH 9. Based on the ability of SSB to suppress R. microporus, results showed that treatment SSB18 applied at 25 mL/seedling (D25) had the lowest disease incidence compared to 50 mL/seedling (D50) and 75 mL/seedling (D75). Meanwhile, SSB16 and SSB21 showed the lowest disease incidence at 50 mL/seedling (D50) and 75 mL/seedling (D75) respectively. Total silica accumulation in plant treated with SSB16, SSB18 and SSB21 were the lowest at 50 mL/seedling (D50), 25 mL/seedling (D25) and 75 mL/seedling (D75) respectively. A correlation analysis between disease suppression and silicon content in root indicated positive association suggesting that disease occurrence increased linearly with silicon accumulation. Lignin content in rubber seedling treated with SSB16, SSB18 and SSB21 were higher in treatment D50 (2.88 mg LTGA g-1), D25 (2.82 mg LTGA g-1) and D75 (3.74 mg LTGA g-1) respectively. Similar trend on the increase of peroxidase enzyme was also shown by SSB16, SSB18 and SSB21 at D50 (4.25 unit mL-1), D25 (10.75 unit mL-1) and D75 (6.88 unit mL-1). Association between both ISR compounds with silicon content in root resulted in negative correlation. Similarly, reduction of disease was also strongly associated with the negative correlation with ISR compounds. Strong positive relationship between lignin and peroxidase reflected that stimulation of peroxidase due to the effect of silicic acid in plant affect lignin formation. Application of SSB significantly increased (P≤0.05) plant growth attributes and fresh plant biomass were significantly affected by the rate with the highest shown by D50 treatment. Application of SSB increased plant nutrient availability particularly potassium with D50 and D75 rates. Hence, results of this study confirmed that organic acids and pH plays important role in silica dissociation and application of SSB had successfully reduced WRD incidence in rubber seedling.